Development of a wind rosette for farmstead planning in Ibadan environ, Nigeria (2011)
The prevailing wind speed and direction in an environment are critical factors in farmstead planning they influence the appropriate location and orientation of structures in order to reduce wind load impact and promote a healthy environment. The failure of farm structures especially with roof blown-off arising from wind load has become rampant in lbadan environ in recent time and an urgent solution is desirable. In this work, an attempt is made to develop a wind rosette for lbadan environ using 20 year climatic data. The prevailing wind direction was established to be southwesterly indicating that it originates in the south western direction and progresses in the northeastern direction while the average wind speed is 1.9m/s. A design speed of 2.1m/s being the highest recorded over the 20 year period is recommended for use in determining wind load. In order to minimize the impact of wind loads, the least projected area of buildings should be oriented in the southeast direction: shelterbelts should also be planted in the southeast direction in order to offer maximum protection. Using this prevailing wind direction as a guide, all odour producing facilities such as livestock units and waste treatment plants should be located on the leeward side of residential buildings.